2006
DOI: 10.3171/jns.2006.105.4.576
|View full text |Cite
|
Sign up to set email alerts
|

Microhemorrhage, a possible mechanism for cyst formation in vestibular schwannomas

Abstract: Intratumoral microhemorrhage is a possible mechanism of pathogenesis in cystic VS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
83
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 27 publications
4
83
0
Order By: Relevance
“…4 Hemosiderin deposition was obvious in all of our cases, and thrombotic vessels and abnormal vessel proliferation were observed in cases 2 and 3. Furthermore, xanthochromic fluid within the cysts was found during surgery, which supports the above hypothesis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…4 Hemosiderin deposition was obvious in all of our cases, and thrombotic vessels and abnormal vessel proliferation were observed in cases 2 and 3. Furthermore, xanthochromic fluid within the cysts was found during surgery, which supports the above hypothesis.…”
Section: Discussionmentioning
confidence: 92%
“…However, the relationship be- tween cystic formation and the distribution of Antoni cell types is not always observed. 4 In cases 2 and 3, cellular Antoni type A tissue occupied most of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…16 By using T2-weighted sequence, Ishii et al 14 demonstrated microhemorrhages in 5 of 12 VS measuring more than 25 mm in diameter. Park et al 15 demonstrated microhemorrhage in 35% of VS in their study by using the T2-weighted sequence, though histopathologic examination revealed hemosiderin in all cases. In our study, T2*-weighted GRE images demonstrated microhemorrhages in 15 of 16 VS, resulting in a sensitivity of 93.8%, a specificity and positive predictive value of 100%, and a negative predictive value of 83.3% with T2*-weighted GRE sequences in the detection of microhemorrhages, whereas T2-weighted TSE and FLAIR sequences showed microhemorrhages in only 2 tumors, resulting in a sensitivity of 12.5%.…”
Section: Discussionmentioning
confidence: 99%
“…13 Neoplastic Schwann cells themselves may show hemosiderin because of their phagocytic properties, similar to macrophages. 13 Although MR imaging is exquisitely sensitive for the detection of microhemorrhage, only a few MR studies in the literature have shown the presence of microhemorrhages in VS. 14,15 The major reason for this could be the use of the T2-weighted sequence, which is inherently less sensitive than the T2*-weighted GRE sequence in the identification of microhemorrhage in these studies. 16 By using T2-weighted sequence, Ishii et al 14 demonstrated microhemorrhages in 5 of 12 VS measuring more than 25 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation